First-trimester Combined Screening Test for Aneuploidies in Brazilian Unselected Pregnancies: Diagnostic Performance of Fetal Medicine Foundation Algorithm - Laila Pinheiro Abi Abib; Renato Augusto Moreira de Sá; Fernando Maia Peixoto-Filho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective The main objective of this study was to examine the diagnostic performance of the first-trimester combined test for aneuploidies in unselected pregnancies from Rio de Janeiro and compare it with the examples available in the literature. Methods We investigated 3,639 patients submitted to aneuploidy screening from February 2009 to September 2015. The examination is composed of the Fetal Medicine Foundation risk evaluation based on nuchal translucency evaluation, mother's age, presence of risk factors, presence of the nasal bone and Doppler of the ductus venous in addition to biochemical analysis of pregnancy-associated plasma protein A (PAPP-A) and beta-human chorionic gonadotropin (β-hCG) markers. The cut-off point for high risk for aneuploidies was defined as greater than 1:100, with intermediate risk defined between 1:100 and 1:1,000, and low risk defined as less than 1:1,000. The variable aneuploidy was considered as a result not only of trisomy of chromosome 21 but also trisomy of chromosomes 13 and 18. Results Excluding the losses, the results of 2,748 patients were analyzed. The firsttrimester combined test achieved 71.4% sensitivity with a 7.4% false-positive (FP) rate, specificity of 92.6%, positive predictive value (PPV) of 6.91% and negative predictive value (NPV) of 99.76%, when the cut-off point considered was greater than 1:1,000. Through a receiving operating characteristics (ROC) curve, the cut-off point that maximized the sensitivity and specificity for the diagnosis of aneuploidies was defined as 1:1,860. When we adjusted the false-positive (FP) rate to 5%, the detection rate for this analysis is 72.7%, with a cut-off point of 1:610. Conclusion The combined test of aneuploidy screening showed a detection rate inferior to those described in the literature for a higher FP rate.